Magnitude and determinants of drug-related problems among patients admitted to medical wards of southwestern Ethiopian hospitals: A multicenter prospective observational study. - Firomsa Bekele; Tesfaye Tsegaye; Efrem Negash; Ginenus Fekadu (PLoS ONE)
Background Drug-related problem (DRP) is an event involving drugs that can impact the patient's desired goal of therapy. In hospitalized patients, DRPs happen during the whole process of drug use such as during prescription, dispensing, administration, and follow-up of their treatment. Unrecognized and unresolved DRPs lead to significant drug-related morbidity and mortality. Several studies conducted in different hospitals and countries showed a high incidence of DRPs among hospitalized patients. Despite the available gaps, there were scanties of studies conducted on DRPs among patients admitted to medical wards in Ethiopia. Therefore, this study assessed the magnitude of drug-related problems and associated factors among patients admitted to the medical wards of selected Southwestern Ethiopian hospitals. Patients and methods A multicenter prospective observational study was conducted at medical wards of Mettu Karl Hospital, Bedele General Hospital and Darimu General Hospital. Adult patients greater than 18 years who were admitted to the non-intensive care unit (ICU) of medical wards and with more than 48 h of length of stay were included. Identified DRPs were recorded and classified using the pharmaceutical care network Europe foundation classification system and adverse drug reaction was assessed using the Naranjo algorithm of adverse drug reaction probability scale. Hill-Bone Compliance to High Blood Pressure Therapy Scale was used to measure medication adherence. Multivariable logistic regression was used to analyze the associations between the dependent variable and independent variables. Result Of the 313 study participants, 178 (56.9%) were males. The prevalence of actual or potential DRPs among study participants taking at least a single drug was 212 (67.7%). About 125 (36.63%) patients had one or more co-morbid disease and the average duration of hospital stay of 7.14 ± 4.731 days. A total of 331 DRPs were identified with an average 1.06 DRP per patient. The three-leading categories of DRPs were unnecessary prescription of drugs 92 (27.79%), non-adherence (17.22%) and dose too high (16.92%). The most common drugs associated with DRPs were ceftriaxone (28.37%), cimetidine (14.88%), and diclofenac (14.42%). The area of residence (AOR = 2.550, 95CI%: 1.238-5.253, p = 0.011), hospital stay more than 7 days (AOR = 9.785, 95CI%: 4.668-20.511, p≤0.001), poly pharmacy (AOR = 3.229, 95CI%: 1.433-7.278, p = 0.005) were predictors of drug-related problem in multivariable logistic regression analysis. Conclusion The magnitude of drug therapy problems among patients admitted to the medical wards of study settings was found to be high. Therefore, the clinical pharmacy services should be established in hospitals to tackle the DTPs in this area. Additionally, healthcare providers of hospitals also should create awareness for patients seeking care from health facilities of the importance of rational drug usage.